Sustainable urban development: a case study on green infrastructure implementation in Kota City India - Lal, Shiv; Choudhary, Saaransh; Kakodia, Ashok Kumar (ASCEE, 2024)
Kota City is known as an educational city with increasing urbanization, requiring a sustainable development approach to address environmental and social challenges. One of the solutions implemented is green infrastructure, which integrates natural elements to improve ecological quality, reduce environmental pressure, and improve people's welfare. This study aims to evaluate the effectiveness of green infrastructure in supporting sustainable development in Kota City. The approaches studied include rainwater management, renewable energy (solar, wind, nuclear, hydro), sustainable transportation, and red light-free zone policies to reduce energy consumption and pollution. The study results show that implementing green infrastructure significantly lowers urban temperatures, improves flood management, improves air quality, and improves energy efficiency. These approaches can help for sustainable urban development. This research provides benefits in the form of a greener, more efficient, and sustainable urban development model. With this approach, Kota city can be an example for other cities in creating a healthier, environmentally friendly environment and improving the economic and social welfare of the community.